Avaliação da ingestão de vitaminas e minerais relacionados a hipertensão arterial sistêmica em uma amostra de hipertensos de um município da Zona da Mata alagoana - Bloom, Maria Inez Tenório (2011)
This review addresses issues relevant to the understanding of systemic hypertension, inasmuch as an epidemic affects a third of the world population, and its role as a risk factor in cardiovascular diseases that are the principle cause of death in Brazil and many other countries; notwithstanding high, medium or low incomes. For the understanding of this process it is important to discuss the nutritional transition in the light of demographic and epidemiological transitions and the change in the dietary patterns of Brazilians over the years. The low consumption of fruits and vegetables (FV), sources of micronutrients, is one of the characteristics of this pattern. Studies have shown an inverse relationship between FV consumption and hypertension. The assessment of this intake is necessary to prevent and correct the possible distortions of it, so that the nutritional demands are met adequately. The Dietary Reference Intakes (DRIs) are reference values of the ingestion of nutrients and are used to plan and evaluate diets. The Estimated Average Requirement (EAR), one of the four values that make up DRIs allows through the process EAR as a cutoff point to estimate the prevalence of nutrient inadequacy in a determined group, an important instrument in the prevention of diseases. Thirteen micronutrients: vitamins (C, E, B6 and folate) and minerals (Na, K, Ca, Mg, Se, Zn, Cu and Fe), associated with hypertension are presented in this work. Finally, within the context of hypertension, it falls to the national policies for primary national health care (PNAB) and health promotion (PNPS), as privileged positions in the health system (SUS), for a reorientation of the model of assistance.